TRADITIONAL ECOLOGICAL KNOWLEGDE OF STINGLESS BEES IN WETLAND AND PEATLAND ECOSYSTEMS OF AN URARINA COMMUNITY IN LORETO, PERU - DÁVILA TUESTA, Wendy (2025)
The traditional knowledge of the Urarina people about native stingless bees (Meliponini) is at risk of disappearing, exacerbated by climate change affecting the floodplain and peatland ecosystems they inhabit. This study documents the identification, traditional uses, ecosystems, associated plants, and knowledge transmission in the Urarina community of Santa Martha, Loreto, Peru, through interviews, focus groups, and field inventories conducted between 2023 and 2024. Seven species of stingless bees were identified, associated with nine species of arboreal plants, primarily used for technological, medicinal, and magical-religious recreational purposes. The local ecosystems "atane" and "leuaku" show greater bee diversity. Knowledge transmission is oral and observational, led by parents and grandparents. This work highlights the importance of Urarina knowledge about bees for ecosystem conservation and underscores the need to strengthen intergenerational knowledge transmission.